Panopticon: A Complete In-DRAM Rowhammer Mitigation - Bennett, Tanj; Saroiu, Stefan; Wolman, Alec; Cojocar, Lucian (1st Workshop on DRAM Security (DRAMSec), 2021)
The shortcomings of previous Rowhammer mitigations prevent their adoption in practice. Their implementations either need signiﬁcant amounts of fast memory, such as CAM or SRAM, or require changes across multiple hardware and software layers. Panopticon is a complete in-DRAM Rowhammer mitigation that is both inexpensive and, for DDR4, requires no changes to any hardware components other than DRAM. Panopticon uses a novel DRAM mat design to implement counters and the DRAM’s row decoding logic to access the row’s corresponding counter. Finally, for DDR4, Panopticon leverages ALERT n to stop a memory controller from issuing new DRAM commands whenever it needs time to refresh potential victim rows.